Gypsy Woman and Spanish cinema. An educational resource - Aparicio Gervás, Jesús M.; Ibáñez Giralda, Carlos A. (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Cinema is one of the best resources that facilitate the transmission of knowledge of a cultural reality, allowing the elimination of prejudices and stereotypes and, in turn, generating spaces for intercultural coexistence. The objective we intend to achieve is to promote the important role of Roma women as a catalyst for the social inclusion of their community. Through a rigorous film selection, we seek to make visible the most significant features of the Roma culture. The results obtained will allow us to deepen their cultural reality may be used as a resource for social intervention in educational contexts.